Testosterone target therapy: focus on immune response, controversies and clinical implications in patients with COVID-19 infection. (April 2021) - Salciccia, Stefano; Del Giudice, Francesco; Eisenberg, Michael L.; Mastroianni, Claudio M.; De Berardinis, Ettore; Ricciuti, Gian Piero; Viscuso, Pietro; Zingaropoli, Antonella; Pasculli, Patrizia; Ciardi, Maria Rosa; Sciarra, Alessandro; Maggi, Martina
The pandemic acute respiratory syndrome coronavirus 2 (SARS-CoV-2) named COVID-19 is causing a severe health emergency, and an individual's hormonal milieu may play an important role in both susceptibility to infection and severity of clinical course. We analyzed the role of testosterone in the immune response, and we hypothesized possible mechanisms to explain the high incidence of COVID-19 infection and a worse clinical course in elderly male patients. Testosterone may impair the immune response, and this effect could explain the greater susceptibility of men to infection. Transmembrane serine protease 2 (TMPRSS2) plays a crucial role in the entry of the virus into the respiratory epithelial cells, leading to COVID-19 disease. It is crucial to emphasize that testosterone levels and chemical castration (e.g. by androgen deprivation therapy for prostate cancer) may have contrasting roles in the phases of COVID-19 infection. Whereas low testosterone levels may be protective against the initial susceptibility (due to a restoration of immunological functions and a block of TMPRSS2), low testosterone may stimulate a worse clinical course in the advanced COVID-19 infection as it could exacerbate or activate the cytokine storm. If testosterone levels play these different roles, it is necessary to carefully identify patients for any indicated testosterone manipulation.